Psychological Climate and Work Engagement in Academia : The Mediating Role of Job Crafting - Kaur, Kanwalpreet; Ahuja, Sunaina; Kumar, Pawan; Saini, Harish (Prabandhan: Indian Journal of Management, 2025)
Purpose : As India envisions becoming a developed nation by 2047, it is imperative to match global higher education standards by improving the quality of training and engagement of faculty members. Hence, this study aimed to create a novel model empirically testing the relationships among psychological climate (PC), job crafting (JC), and work engagement in higher education. Methodology : The cross-sectional data were collected from a sample of 442 academics employed in 32 universities in India. Partial least squares structural equation modeling was applied to investigate the proposed conceptual model in higher education institutions. Findings : PC directly predicted JC and work engagement. JC positively and significantly mediated the PC-work engagement association. A positive PC triggered the job-crafting behavior of academics, enabling them to go the extra mile and demonstrate high levels of work engagement. Practical Implications : When academic institutions emphasize enhancing the PC, academics perceive that their well-being is a matter of concern, and they reciprocate by improving their teaching and research-related activities through JC, further leading to an augmented level of work engagement. Originality : This study offered a novel model at the disposal of the higher education sector to have suitable policies nurturing the PC of academics, leading to JC and work engagement, which could be a key contributor to the sustainable development of the Indian higher education sector.